Obstetrician involvement in planned midwife-led births: a cohort study in an obstetric department of a University Hospital in Switzerland - Ann-Katrin Morr; Nicole Malah; Andrea Manuela Messer; Annina Etter; Martin Mueller; Luigi Raio; Daniel Surbek (BMC, 2021)
Abstract Background Healthy women with low risk singleton pregnancies are offered a midwife-led birth model at our department. Exclusion criteria for midwife-led births include a range of abnormalities in medical history and during the course of pregnancy. In case of complications before, during or after labor and birth, an obstetrician is involved. The purpose of this study was 1) to evaluate the frequency of and reasons for secondary obstetrician involvement in planned midwife-led births and 2) to assess the maternal and neonatal outcome. Methods We analyzed a cohort of planned midwife-led births during a 14 years period (2006-2019). Evaluation included a comparison between midwife-led births with or without secondary obstetrician involvement, regarding maternal characteristics, birth mode, and maternal and neonatal outcome. Statistical analysis was performed by unpaired t-tests and Chi-square tests. Results In total, there were 532 intended midwife-led births between 2006 and 2019 (2.6% of all births during this time-period at the department). Among these, 302 (57%) women had spontaneous vaginal births as midwife-led births. In the remaining 230 (43%) births, obstetricians were involved: 62% of women with obstetrician involvement had spontaneous vaginal births, 25% instrumental vaginal births and 13% caesarean sections. Overall, the caesarean section rate was 5.6% in the whole cohort of women with intended midwife-led births. Reasons for obstetrician involvement primarily included necessity for labor induction, abnormal fetal heart rate monitoring, thick meconium-stained amniotic fluid, prolonged first or second stage of labor, desire for epidural analgesia, obstetrical anal sphincter injuries, retention of placenta and postpartum hemorrhage. There was a significantly higher rate of primiparous women in the group with obstetrician involvement. Arterial umbilical cord pH < 7.10 occurred significantly more often in the group with obstetrician involvement, while 5' Apgar score < 7 did not differ significantly. The overall transfer rate of newborns to neonatal intensive care unit was low (1.3%). Conclusion A midwife-led birth in our setting is a safe alternative to a primarily obstetrician-led birth, provided that selection criteria are being followed and prompt obstetrician involvement is available in case of abnormal course of labor and birth or postpartum complications.